2018
DOI: 10.1159/000494139
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic Acid Ameliorates Lipopolysaccharide-Induced Depression Like Behavior in Mice via the Inhibition of Neuroinflammation and Oxido-Nitrosative Stress

Abstract: Depression is a mental disease that causes severe economic and social burdens. The mechanism for the onset of depression remains largely unknown. Recently, more and more attention is being given to the role of neuroinflammation and oxidative stress in depression. Tauroursodeoxycholic acid (TUDCA), a clinically available agent used to treat cholesterol gallstone and protect neurons against neurodegeneration, has been reported to prevent neuroinflammation and oxidative stress. In this study, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Although there were limitations, the current findings still highlighted a potential contribution of PCS in the development of depression in this rodent model. The etiology of depression is multifactorial, including genetic, environmental, and dietary factors, particularly chronic stress and diseases [ 5 , 6 , 26 , 28 ]. Accumulating evidence highlights the pathogenic roles of oxidative stress, neuroinflammation, impaired neurogenesis, as well as dysregulated neurotransmitters and neurohormonal pathways in the development and progression of depression [ 6 , 23 , 24 , 25 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there were limitations, the current findings still highlighted a potential contribution of PCS in the development of depression in this rodent model. The etiology of depression is multifactorial, including genetic, environmental, and dietary factors, particularly chronic stress and diseases [ 5 , 6 , 26 , 28 ]. Accumulating evidence highlights the pathogenic roles of oxidative stress, neuroinflammation, impaired neurogenesis, as well as dysregulated neurotransmitters and neurohormonal pathways in the development and progression of depression [ 6 , 23 , 24 , 25 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…CNS diseases are accompanied by a series of biochemical and molecular changes, resulting in acute and long-term impacts on both behavioral and neurological functions. Changes in blood–brain barrier permeability, oxidative stress, neuroinflammation, neurochemicals, neurotrophins, neurogenesis, apoptosis, and synaptic connection are frequently presented in most neurological diseases [ 5 , 6 ]. In rodent models with CKD caused by adenine feeding or a 5/6 nephrectomy, the experimental animals have shown depression- and anxiety-like behaviors concurrent with an impaired blood–brain barrier and the cerebral activation of oxidative stress and neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies have revealed that the increased proinflammatory cytokine can trigger oxido-nitrosative stress, a pathological event that could be observed in depressed patients, thereby promoting depression onset and/or progression [15][16][17][18][19]. Previous studies have also found that hippocampus and prefrontal cortex are the key regions of the brain, closely associated with mood and behavior regulation [20,21], and more importantly many compounds that are being studied in preclinical trials have been shown to ameliorate depression-like behaviors in rodents via interfering with neuroinflammatory response and oxido-nitrosative stress in the hippocampus and prefrontal cortex [10,11,22]. Therefore, suppression of neuroinflammation and oxido-nitrosative stress, especially in the hippocampus and prefrontal cortex, may be a potential strategy for depression treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the filtered liquids were concentrated under pressure at 60˚C and stored at 4˚C. tauroursodeoxycholic acid (TUDCA) is a water-soluble bile acid that is commonly used in clinical settings (30) and was provided by Bruschettini S.R.L. TUDCA was used as the positive control drug in the present study.…”
Section: Methodsmentioning
confidence: 99%